2017
DOI: 10.2147/ijn.s133971
|View full text |Cite
|
Sign up to set email alerts
|

Linseed hydrogel-mediated green synthesis of silver nanoparticles for antimicrobial and wound-dressing applications

Abstract: Polysaccharides are being extensively employed for the synthesis of silver nanoparticles (Ag NPs) having diverse morphology and applications. Herein, we present a novel and green synthesis of Ag NPs without using any physical reaction conditions. Linseed hydrogel (LSH) was used as a template to reduce Ag + to Ag 0 . AgNO 3 (10, 20, and 30 mmol) solutions were mixed with LSH suspension in deionized water and exposed to diffused sunlight. React… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 39 publications
2
27
0
1
Order By: Relevance
“…74 The linseed hydrogel was another choice for the green synthesis of AgNPs, possessing the advantages of increasing the wound closure percentage and also the collagen content at the wound site. 60 Cassia auriculata L.-mediated AgNPs were effective on both incision and excision wound models in Wistar albino rats. Although the wound healing activity of Cas.…”
Section: Green-synthesized Metal Nanoparticles Using Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…74 The linseed hydrogel was another choice for the green synthesis of AgNPs, possessing the advantages of increasing the wound closure percentage and also the collagen content at the wound site. 60 Cassia auriculata L.-mediated AgNPs were effective on both incision and excision wound models in Wistar albino rats. Although the wound healing activity of Cas.…”
Section: Green-synthesized Metal Nanoparticles Using Plantsmentioning
confidence: 99%
“…The most common metallic nanoparticles in biomedical and medicinal applications are silver-and gold-based nanostructures (nanoparticles, nanocomposites, and nanocoating), which have drawn the attention of researchers. Silver nanoparticles (AgNPs) and different silver salts have recently intrigued medical scientists in the fields of clinical and fundamental researches due to their excellent antibacterial and antimicrobial activities, 60 which could be attributed to their large surface area to volume ratio, and could be remarkably interesting due to growing microbial resistance against metal ions, antibiotics, and the development of resistant strains. 61 In addition to these characteristics, these nanoparticles possess the advantages of high chemical stability, antiviral, antifungal, and anti-inflammatory activities, and possibility to be incorporated into different composite structures, cosmetic products, food industry, and so on.…”
Section: Green-synthesized Metal Nanoparticles Using Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Researchers have explored polysaccharides (i.e., non-toxic, biodegradable and economical reagents) 17,18 such as hydroxypropylcellulose, 19 dextran, 20 cellulose, 21 and chitosan 22 as reducing and stabilizing agents for the green synthesis of Ag NPs. Among polysaccharides, naturally occurring water swellable polysaccharides like arabinoxylans 23 and rhamnogalacturonan 24 are being explored nowadays for green synthesis of silver nanoparticles (Ag NPs) having diverse morphology and potential biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was suggested that these particles have potential wound healing applications [112]. Other studies using hydrogel-mediated polysaccharide-based (e.g., linseed, chitosan, or Glucuronoxylan isolated from seeds of Mimosa pudica) AgNPs have also shown wound healing capabilities, mainly due to their antimicrobial characteristics and stimulation of the reepithelialization and granulation tissue formation [15,113].…”
Section: Wound Healing Properties Of Polysaccharide-based Agnpsmentioning
confidence: 99%